A Reduced Graphene Oxide/Disodium Terephthalate Hybrid as a High‐Performance Anode for Sodium‐Ion Batteries. Issue 65 (3rd November 2017) - Cao, Tengfei; Lv, Wei; Zhang, Si‐Wei; Zhang, Jun; Lin, Qiaowei; Chen, Xiangrong; He, Yanbing; Kang, Fei‐Yu; Yang, Quan‐Hong
Abstract: As a promising candidate for large‐scale energy storage systems, sodium‐ion batteries (SIBs) are experiencing a rapid development. Organic conjugated carboxylic acid anodes not only have tailorable electrochemical properties but also are easily accessible. However, the low stability and electrical conductivity hamper their practical applications. In this study, disodium terephthalate (Na2 TP), the most favorable organic conjugated carboxylic acid anode material for SIBs, was proposed to integrate with graphene oxide (GO) by an anti‐solvent precipitation process, which ensures the uniform and tight coating of GO on the Na2 TP surface. GO is electrochemically reduced during the first several cycles of the electrochemical measurement, which buffers the volume change and improves the electrical conductivity of Na2 TP, resulting in a better cyclic and rate performance. The incorporation of only 5 wt % GO onto Na2 TP leads to a reversible capability of 235 mA h g −1 after 100 cycles at a current rate of 0.1 C, which is the best among the state of the art organic anodes for SIBs. The one‐step synthesis together with the low costs of the raw materials show a promise for the scalable preparation of anode materials for practical SIBs. Abstract : Nice wrap : Graphene oxide (GO) wrapped around disodium terephthalate (Na2 TP) is prepared through an anti‐solvent precipitation method (see figure). GO is reduced during the first several cycles of charge/discharge leading to an outstanding cyclic performance of the GO/Na2 TP hybrid as an anode for sodium‐ion batteries.